An Analysis on the Role of Student Association of Siyasah Department in Political Education at Public Islamic University of Sumatera Utara - Purba, Mhd Hafizal Ashari; Lubis, Suwardi; Maas, Linda Trimurni (Budapest International Research and Critics University, 2021)
The Research used descriptive qualitative method with student political education through Student Association in general. The data were gathered by conducting library research, interviews, and documentary study. Political education is highly needed for a dynamic life of the nation. However, it has a problem since there is imbalance in political development, especially in political socialization with economic development in national development which a part of political socialization in its process. The imbalance is the effect of political participation which does not achieve it totality. The objective of the research was to find out the development of student political education and some efforts to solve obstacles and the dynamics of the development. Besides that, this research was intended to find out the role student association increasing their knowledge and mentality in establishing their intellectual. This research was also expected to be the reference in increasing student political education. It could be concluded that Student Association of Siyasah and Law Department, UIN (Public Islamic University) of Sumatera Utara had done its task ad function well through student affairs programs and is considered successful in guarding the process of student political education. This success is closely related to cooperation between students and the officials in campus in guarding student affairs programs.